BANKING DENSITY AND ITS RELATIONSHIP TO ENHANCING THE VOLUME OF BANK DEPOSITS-ANALYTICAL RESEARCH FOR THE IRAQI BANKING SECTOR (American Journal of Business Management, Economics and Banking, 2024)
The strength and development of the banking sector is a major criterion for judging the soundness of the economy and its ability to attract local and foreign deposits, and based on the principle of deposits being the basic source and vital lifeline for the work of banks, the banking system is the backbone of the economy, and from this standpoint the aim of the research is to test the effect of banking density as an independent variable across its dimensions. (The number of branches, the number of accounts at banks, the number of electronic cards, the number of ATMs, the number of point-of-sale devices) in enhancing the volume of bank deposits as a dependent variable with its dimensions represented by (total deposits, current deposits, fixed deposits, and savings deposits). If the problem of the research is represented by the reluctance of capital owners to deposit in banks due to the weakness of the means of attraction by the banks. The importance of the research stems from the role played by the increasing volume of bank deposits, which are the largest and least expensive source of financing than other sources of financing, in meeting the requirements of development and increasing the efficiency of the banking sector, which in turn drives the wheel of trade and economy for the country. For the purpose of achieving the objectives of the research, I rely on data related to the official research with observations. Monthly reports for the years 2017-2021, which were processed in the ECXEL program and the formulation of hypotheses that were tested using statistical methods (EVIEWS10, SPSS V.23).